FAE1 and FAD2 gene expression dynamics and fatty acid modulation in Brassica under salt stress: A molecular insight - Samia Fatima; Nadia Iqbal; Shengqiao Lu; Muhammad Omar Khan; Muhammad Aamer Mehmood; Sameer H. Qari; Atif Jamal; Zhengyi Wei; Niaz Ahmad (PLoS ONE, 2026)
Brassica species are major oilseed crops valued for their high seed oil content; however, salinity severely limits their growth, productivity, and oil quality. Since membrane stability and oil composition are primarily governed by fatty acid metabolism, this study focused on two key lipid biosynthesis genes, FAE1 ( Fatty Acid Elongase 1 ) and FAD2 ( Fatty Acid Desaturase 2 ), to elucidate their role under NaCl-induced stress. Understanding the regulatory and functional behavior of these genes under salinity is essential for developing salt-resilient Brassica cultivars capable of maintaining oil quality on saline soils. To establish a mechanistic foundation, gene and protein sequences of FAE1 and FAD2 were retrieved from publicly available genomic databases. Various bioinformatics analyses were conducted to identify conserved domains, structural integrity, phylogenetic relationships, and regulatory features, thereby verifying their functional relevance in fatty acid biosynthesis. Promoter regions were also examined for stress-responsive cis-acting elements, including dehydration-responsive elements (DRE) and ABA-responsive elements (ABRE), providing predictive evidence of transcriptional regulation under salt stress. Based on these computational predictions, controlled salt stress was imposed to experimentally evaluate gene responsiveness and physiological adaptation. Tissue-specific expression analysis revealed significant differential regulation of FAE1 and FAD2 under salt stress, with pronounced transcriptional modulation observed in developing siliques and leaves compared to roots. Salt stress caused a dose-dependent reduction in growth attributes and yield-related traits in both species. Two-way ANOVA revealed significant NaCl effects on yield parameters ( F = 6.6–20, P < 0.05), with seed yield declining by approximately 25–35% at 200 mM NaCl, with comparatively higher yield stability in B. juncea than in B. napus under salinity. Seed quality analysis showed species-specific responses in oil and protein content, whereas most fatty acids, including erucic acid, remained relatively stable. Despite transcriptional modulation of both genes, the overall fatty acid profile exhibited limited variation, suggesting metabolic buffering within the lipid biosynthetic network. Together, this integrative approach links in silico predictions with experimental validation, establishing a continuum from gene structure and regulation to phenotypic performance and seed quality. These findings enhance our understanding of lipid metabolism–mediated salt stress adaptation and provide a foundation for breeding and genome-editing strategies aimed at improving oilseed stability in Brassica under saline conditions.